XXVI Brazilian Congress on Biomedical Engineering : CBEB 2018, Armação de Buzios, RJ, Brazil, 21-25 October 2018.: CBEB 2018, Armação de Buzios, RJ, Brazil, 21-25 October 2018. (Vol. 1) ([2019]) - Unknown
No abstract available